2000
DOI: 10.1007/pl00008153
|View full text |Cite
|
Sign up to set email alerts
|

Simulating ozone detoxification in the leaf apoplast through the direct reaction with ascorbate

Abstract: This paper presents a mathematical model which enables the semi-quantification of ozone (O3) detoxification, based upon the direct reaction of the pollutant with ascorbate (ASC) located in the aqueous matrix associated with the cell wall (i.e. the apoplast). The model describes the uptake of ozone into the leaf and its direct reaction with ASC, taking into consideration the regeneration of dehydroascorbic acid in the cytosol, the rate of replenishment of cell wall ASC and the distribution of ASC between sub-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(86 citation statements)
references
References 101 publications
3
81
0
Order By: Relevance
“…The induction of gene expression in ozone stress was significantly lower in the tolerant SL41 than in cv Nipponbare (Frei et al, 2010). From a physiological point of view, apoplastic ascorbate (AsA) has been shown to form the first line of defense against the ozone entering the plants through the stomata (Luwe et al, 1993;Plöchl et al, 2000;Feng et al, 2010), which supports the link between the annotation of the candidate gene and ozone stress tolerance. In line with this concept, a previous study demonstrated that an AO-overexpressing tobacco (Nicotiana tabacum) plant negatively affected tolerance to ozone due to altered apoplastic reduced AsA content and AsA redox status (Sanmartin et al, 2003).…”
mentioning
confidence: 64%
“…The induction of gene expression in ozone stress was significantly lower in the tolerant SL41 than in cv Nipponbare (Frei et al, 2010). From a physiological point of view, apoplastic ascorbate (AsA) has been shown to form the first line of defense against the ozone entering the plants through the stomata (Luwe et al, 1993;Plöchl et al, 2000;Feng et al, 2010), which supports the link between the annotation of the candidate gene and ozone stress tolerance. In line with this concept, a previous study demonstrated that an AO-overexpressing tobacco (Nicotiana tabacum) plant negatively affected tolerance to ozone due to altered apoplastic reduced AsA content and AsA redox status (Sanmartin et al, 2003).…”
mentioning
confidence: 64%
“…Species with low LMA are more reactive to environmental stimuli and also more sensitive to stress compared with species with high LMA, which are more stress tolerant (Bussotti, 2008). As leaves with lower LMA tend to have greater internal air spaces for diffusion to occur, more cell surface area is exposed to ozone and reactive oxygen species (ROS) internally, and most likely there is also a lower ability to produce anti-oxidants due to fewer cells and thinner cell walls (Plochl et al, 2000). In addition, a higher g s implies a higher flux of ozone to the intercellular space, and g s of clone 546 was higher than that of clone 107 under the same treatment and period.…”
Section: Discussionmentioning
confidence: 99%
“…Rautenkrantz et al (1994) exposed purified barley protoplasts to various ASC concentrations and observed a saturation type uptake kinetics. From these data, Plöchl et al (2000) calculated a maximum uptake rate of 0.013 nmol m −2 plasmalemma s −1 . Foyer & Lelandais (1996) reported a maximum value of 0.34 nmol m −2 plasmalemma s −1 for isolated pea protoplasts.…”
Section: Asc Consumption Vs Supplymentioning
confidence: 99%